2020
DOI: 10.1002/fsn3.1492
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coenzyme Q10 supplementation on oxidative stress: A systematic review and meta‐analysis of randomized controlled clinical trials

Abstract: Some evidence exists in supporting the beneficial effects of coenzyme Q10 (CoQ10) on oxidative stress. Since the findings of studies over the impact of CoQ10 supplementation on oxidative stress are contradictory, this study was conducted. The aim was to evaluate CoQ10 supplementation effect on total antioxidant capacity (TAC), malondialdehyde (MDA), glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) levels using data collected from randomized controlled trials (RCTs). Several database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
4
29
1
Order By: Relevance
“…Coenzyme Q 10 (CoQ 10 ) is a dietary compound with established antioxidant properties and is increasingly investigated for its ameliorative effects against various metabolic complications. Evidence from other RCTs has been synthesized to inform on the impact of CoQ 10 on inflammation, oxidative stress, or insulin resistance [28][29][30][66][67][68], including its modulation of adiponectin [31]. However, the current meta-analysis provides novel findings on the broad effects of this compound on the regulation of various adipokines on diverse metabolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme Q 10 (CoQ 10 ) is a dietary compound with established antioxidant properties and is increasingly investigated for its ameliorative effects against various metabolic complications. Evidence from other RCTs has been synthesized to inform on the impact of CoQ 10 on inflammation, oxidative stress, or insulin resistance [28][29][30][66][67][68], including its modulation of adiponectin [31]. However, the current meta-analysis provides novel findings on the broad effects of this compound on the regulation of various adipokines on diverse metabolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals suffering from a wide range of illnesses, researchers have also reported reductions in reactive oxygen and nitrogen species levels (ROS/RNS), protein carboxylation, DNA damage, protein nitration, and lipid peroxidation following CoQ10 supplementation [ 33 , 34 ]. Other in vivo evidence of reduced levels of oxidative and nitrosative stress following CoQ10 supplementation includes downregulation of iNOS enzyme and NF-kB [ 35 , 36 ]. Coenzyme Q10 has been shown to reduce markers of systemic inflammation in several metabolic, autoimmune, and neurological disorders [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…CoQ10 is one of the representative antioxidants. Several studies have shown that CoQ10 treatment significantly increased the CAT activity, improved preantral follicles viability, and protected ovarian reserve by inhibiting oxidative stress (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%